STUDY ON INTENSITY EXPRESSION MEASUREMENT AND QUALITY - Rustamova Shakhnoza Abdurakhimovna (Western European Studies, 2024)
In the realm of linguistics, the concept of intensity holds great importance as it profoundly influences the perception, significance, and effectiveness of communication. The expression of intensity in speech is frequently conveyed through various means such as stress, emphasis, intonation, and the semantic and pragmatic strength of words and phrases. This scholarly article thoroughly investigates the measurement and evaluation of intensity expression, shedding light on its significance in the domains of linguistic research, speech analysis, and language quality assessment
Keywords: acoustic intensity; falling intonation; emphasis